Objective evaluation of bone conduction auditory evoked potentials - Hernández Cordero, María del Carmen; Pérez Abalo, María Cecilia (Auditio, 2021)
The objective evaluation of sound conduction through the bone in children has been a subject little reported in the literature. The interpretation of its result, determining the difference with the airway, makes it possible to obtain the air-bone gap, an important variable for making the differential diagnosis of hearing loss. The characterization of bone thresholds using the Brainstem Auditory Evoked Potentials as a method, either with the click stimulus or short tones, has been a topic with little diffusion in clinical audiology, because the response obtained presents changes in morphology and is difficult to recognize, requiring great expertise to identify it at intensities close to the threshold. The Steady-State Auditory Evoked Potentials constitute an appropriate alternative for the evaluation of the bone route, due to the use of modulated tones as stimuli; which are not affected when passing through the bone transducer and because the response is detected automatically, which reduces the bias introduced by the evaluator when visually identifying the electrophysiological threshold